Merle Antony Tuve papers - Tuve, Merle Antony, 1901-1982.; Whitman, Winifred Gray.
Correspondence, memoranda, speeches, articles, reports, laboratory and personal notebooks, notes, personnel records, printed material, blueprints, diagrams, photographs, and other papers relating to Tuve's administration of government-sponsored scientific projects such as the development of the proximity fuze for the U.S. Navy during World War II.
Documents his work as director (1945-1946) of the Applied Physics Laboratory at Johns Hopkins University and as director (1946-1966) of the Dept. of Terrestrial Magnetism of the Carnegie Institution of Washington, as well as his involvement with the International Geophysical Year, National Academy of Sciences, National Radio Astronomy Observatory, Greenbank, W. Va., and a conference on theoretical physics, Washington, D.C. (1939-1940). Subjects include astronomy, composition of the upper atmosphere, cosmic ray flares, geomagnetism, high voltage, conversion of war industries to peacetime uses, magnetism, physics, nuclear physics, seismology, and the Van de Graaff generator. Includes scientific notebooks (1930-1931) of his wife, Winifred Gray Whitman, who collaborated with Tuve in analyzing the effect of high frequency resonance radiation on animals.
Correspondents include Vannevar Bush, Sir J. A. Fleming, Lawrence Hafstad, John C. Merriam, Howard Tatel, Robert Jemison Van de Graaff, Carl Van Doren, and James Lloyd Weatherwax.
Physicist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bush, Vannevar, -- 1890-1974 -- Correspondence; Fleming, J. A. -- Sir, -- 1849-1945 -- Correspondence; Hafstad, Lawrence, -- 1904- -- Correspondence; Merriam, John C. -- 1869-1945 -- Correspondence; Tatel, Howard E. -- 1913- -- Correspondence; Van de Graaff, Robert Jemison, -- 1901-1967 -- Correspondence; Van Doren, Carl, -- 1885-1950 -- Correspondence; Weatherwax, James Lloyd, -- 1884- -- Correspondence; Carnegie Institution of Washington. -- Department of Terrestrial Magnetism; Johns Hopkins University. -- Applied Physics Laboratory; National Academy of Sciences (U.S.); National Radio Astronomy Observatory (U.S.); Astronomy; Atmosphere, Upper; Cosmic rays; Defense industries; Electricity; Geomagnetism; Geophysics -- International cooperation; High voltages; International Geophysical Year, 1957-1958.; Nuclear physics; Physics; Physics -- Washington (D.C.) -- Congresses; Proximity fuzes; Radiation; Science -- Societies, etc; Seismology; Van de Graaff generator; World War, 1939-1945 -- Science; Physicists